Viscoelastic anomaly accompanying anti-crossing behaviour in liquid As2Se3. (22nd June 2018) - Inui, M; Baron, A Q R; Kajihara, Y; Matsuda, K; Hosokawa, S; Kimura, K; Tsuchiya, Y; Shimojo, F; Yao, M; Tsutsui, S; Ishikawa, D; Tamura, K
Abstract: We investigate the dynamic structure factor of the melt of the well known glass former, As2 Se3, using inelastic x-ray scattering for temperatures, T, K and momentum transfers Q from nm −1 . An anomaly was observed at Q = 2.7 nm −1 ( K) with, in the context of a simple model, both an abrupt change in frequency and an increased linewidth reminiscent of an anti-crossing in a solid. Comparison with structural information from reverse Monte Carlo modeling of x-ray diffraction data allows us to associate the disappearance of the anomaly at higher temperatures with a drop in the number of mechanical constraints per atom, n mc, to reminiscent of the threshold applicable for glass formation in rigidity theory. It is inferred that the surprising jump in the dispersion in the liquid may be correlated with a stiffness transition in a network glass.